Simulated Annealing Algorithm for Friction Parameters Identification - Qiang Chen; Junwei Bao; Minzhuo Wang; Haonan Ye; Fuqiang Peng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The present study is concerned with friction parameters identification in the pushing system of projectile of large caliber cannon howitzer. Coulomb model (CM) is adapted to build friction model in the process of pushing projectile. Random direction search algorithm (RDSA) is probably to get into the local best because of the large number of parameters to identify. So simulated annealing algorithm (SAA) based on continuous search space (CSAA) and based on discrete search space (DSAA) is applied to identify friction parameters. The identification results show that both CSAA and DSAA have better accuracy and convergence than RDSA, and CSAA has better accuracy than DSAA. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1893